Report of the Working Group on Tribal development During Seventh Plan 1985-90 - Planning Commission (Planning Commission, Government of India, 1984)
The Report on Tribal Development during the Seventh Plan (1985–1990) provides a comprehensive framework for enhancing the socio-economic conditions of Scheduled Tribes (STs) in India, building upon achievements of the Sixth Plan (1980–1985). Key accomplishments include increased financial investment, expanded coverage of tribal sub-plans, poverty alleviation initiatives, and improved monitoring and evaluation mechanisms. For the Seventh Plan, the report emphasizes tribal empowerment, productivity enhancement in agriculture, animal husbandry, and forestry, educational and human resource development, protection against exploitation, and special attention to vulnerable groups such as primitive tribes and forest dwellers. Financial allocations include Rs. 1,500 crores under Special Central Assistance, supplemented by targeted investment of Rs. 13,000 crores to ensure effective implementation. Administrative recommendations advocate for efficient fund management, non-divertibility of Tribal Sub-Plan (TSP) resources, establishment of tribal cells across ministries, and loan support mechanisms. Emphasis is placed on community participation, family-oriented schemes, and preservation of traditional governance structures. In agriculture, strategies focus on soil and water management, technology adoption, market access, horticulture development, and irrigation infrastructure. Education and health initiatives prioritize literacy, vocational training, preventative healthcare, and integration of traditional medicinal knowledge. Special attention is recommended for women’s development and cultural preservation, alongside systematic monitoring and evaluation to ensure program effectiveness. Overall, the report provides a multi-sectoral, community-engaged approach to tribal development, aiming for sustainable socio-economic upliftment, equitable access to resources, and protection of tribal rights and cultural identity.
Government of India, Planning Commission, December 1984
Keywords: Tribal Development; Scheduled Tribes; Seventh Plan; Socio-Economic Upliftment; Tribal Agriculture; Education; Healthcare; Infrastructure; Community Participation; Poverty Alleviation; Cultural Preservation; Tribal Sub-Plan